(untitled) (Academicia Globe: Inderscience Research, 2022)
Terminological resources have traditionally focused on terms referring to entities, thereby ignoring other important concepts (processes, events and properties) in specialized fields of knowledge. Consequently, large parts of the conceptual structure of these fields are not taken into consideration nor represented. In this article, we show how terms that refer to processes and events (and, to a lesser extent, properties) can be characterized using Frame Semantics (Fillmore, 1982) and the methodology developed. Frames are unveiled first by comparing similarities between the argument structures of terms already recorded in a terminological database and the relationships they share with other terms. A comparison is also carried out with the lexical units. Then, relations between frames are defined that allow us to build small conceptual scenarios that are specific to the field of the environment. This article reports on the methodology, the frames defined up to now and two specific conceptual scenarios.